2018
DOI: 10.1007/s10103-018-2624-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of high-intensity laser therapy in comparison with conventional physiotherapy and exercise therapy on pain and function of patients with knee osteoarthritis: a randomized controlled trial with 12-week follow up

Abstract: Knee osteoarthritis (KOA) is one of the most common musculoskeletal disorders causing pain and functional impairment. The purpose of the study is to compare the effects of high-intensity laser therapy (HILT), conventional physical therapy (CPT), and exercise therapy (ET) on pain and function in patients with KOA. The study was designed as an assessor-blind randomized controlled trial. Ninety-three patients (aged between 50 and 75 years) with proved KOA were included and randomly allocated into three groups, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(106 citation statements)
references
References 36 publications
9
92
2
3
Order By: Relevance
“… 13 15 Meanwhile, numbers of empirical studies have also demonstrated that exercise therapy could improve the quality of patients’ life, effectively relieve the pain and promote functional recovery. 16 18 However, poor long-term adherence is a serious problem that affects the therapeutic effect of exercise treatment. 19 Apart from the aforementioned therapies, as a complementary therapy, acupuncture has become a favorable option for KOA treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 13 15 Meanwhile, numbers of empirical studies have also demonstrated that exercise therapy could improve the quality of patients’ life, effectively relieve the pain and promote functional recovery. 16 18 However, poor long-term adherence is a serious problem that affects the therapeutic effect of exercise treatment. 19 Apart from the aforementioned therapies, as a complementary therapy, acupuncture has become a favorable option for KOA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study were in line with other studies that found pulsed Nd:YAG laser therapy superior to conventional therapy for the improvement of joints function and decrease pain. 15,27,[32][33][34] Despite the benefits exercises, patients with chronic pain often reduced their mobility or refrain to do any physical activities to avoid pain. This leads to muscle weakness, decrease range of motion, increase joint stiffness and decrease physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Data for OA was available in greater number than for RA, in fact, a paucity of information on the efficacy of LLLT for the treatment of RA was evidenced. This difference in the articles found can be explained by the prevalence of the two diseases since OA is more prevalent than RA [42,43]. In Brazil, OA prevalence rate is 4.14%, whereas RA rate is 0.46% [8] RA is a chronic and progressive systemic rheumatologic disease, mainly affecting joints, also presenting extra-joint manifestations [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…There is plenty of confusion between the parameters of energy per point, energy density and energy per treatment, which makes the use of this data unfeasible without proper examination via calculations. Some studies [25,28,31,35,37,[41][42][43] had few parameters of use of the resource, both making it impossible to calculate the dosimetry, and impairing reproducibility, thus compromising its methodological quality.…”
Section: Discussionmentioning
confidence: 99%